The Relevance of Transformational Leadership Values in Modern Organizations - Widia; Fetmawati; Nurhizrah Gistituati; Anisah (Mudir: Jurnal Manajemen Pendidikan, 2025)
In an era of globalization, digitalization, and rapid organizational change, transformational leadership has emerged as an increasingly relevant and necessary leadership model. Transformational leadership emphasizes core values such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These values directly contribute to the development of a dynamic, adaptive, and innovative organizational culture. Transformational leaders do not merely direct; they inspire and guide team members to exceed their performance limits through a compelling vision and ethical role modeling. This article explores in depth how transformational leadership values serve as key elements in enhancing productivity, employee loyalty, sustainable innovation, and in building trust and integrity within modern organizations. In an increasingly complex and multicultural work environment, transformational leaders are capable of aligning individual goals with the organization’s vision. Through a human-centered approach, they act as catalysts for change and reformers in contemporary organizational management. Therefore, the application of transformational leadership values is not only important but has become a strategic necessity for the sustainability and competitiveness of today’s organizations.